A Simulation Study of Chemically Enhanced Water Alternating Gas (CWAG) Injection - Majidaei, S. (2012)
Water alternating gas (WAG) injection has been a default method for commercial gas injection projects worldwide. The injection of water and gas alternatively offers better mobility control of gas and hence, improves the volumetric sweep efficiency. Although the WAG process is conceptually sound, its field incremental recovery rarely exceeds 5 to 10 % OOIP which is disappointing. Apart from operational problems, the WAG mechanism suffers from inherent challenges such as water shielding, gravity segregation, mobility control in high viscosity oil, decreased oil relative permeability, and decreased gas injectivity. This paper addresses the aforementioned problems and proposes a new combination method, named as the chemically enhanced water alternating gas (CWAG), to improve the efficiency of WAG process. The unique feature of this new method is that it uses alkaline, surfactant, and polymer as a chemical slug which will be injected during WAG process to reduce the interfacial tension (IFT) and improve the mobility ratio. In a CWAG process, a chemical slug is chased by water, preceded by gas slug and followed by alternate CO2 and water slug. The importance of CWAG is a combination of the mechanisms involved in chemical flooding and immiscible carbon dioxide (CO2) injection. These mechanisms are IFT reduction, reducing water shielding effect, mobility control, oil viscosity reduction due to the CO2 dissolution and oil swelling. CMG's STARS was used to study the performance of the new method using some of the data found in the literature. It is a chemical flood simulator that can simulate all aspects of chemical flooding, and it also can handle immiscible CO2 injection features by considering K-value partitioning. The sensitivity analysis shows that the new method gives a better recovery when compared to conventional WAG and chemical flooding alone. This study shows the potential of CWAG to enhance the oil recovery.